Time interval of revaccination with 23-valent pneumococcal polysaccharide vaccine more than 5 years does not affect the immunogenicity and safety in the Japanese elderly - Kenji Kawakami; Hiroyuki Kishino; Shinichi Kanazu; Kenichi Takahashi; Tomoharu Iino; Miyuki Sawata; Luwy Musey (Taylor & Francis Group, 2018)
In the previous study, revaccination with 23-valent pneumococcal polysaccharide vaccine (PPSV23) in a total of 161 elderly subjects (≥70 years of age) who had received the initial vaccination at least 5 years before (range: 5 to11 years) showed an acceptable safety profile and induction of immune responses to the serotypes in PPSV23. The optimal interval between the initial vaccination and revaccination with PPSV23 is of interest to protect elderly from pneumococcal disease over the long-term. In this post-hoc analysis, we analyzed that the immunogenicity and safety of revaccination with PPSV23 by time interval after the initial vaccination. The level of serotype-specific immunoglobulin G (IgG) geometric mean concentrations (GMCs) and opsonophagocytic killing activity (OPA) geometric mean titers (GMTs) at 4 weeks after revaccination with PPSV23 in each subgroup based on time interval (5, 6, 7, 8 and 9-11 years) after the initial vaccination were comparable to those after the primary vaccination and vaccine-induced serotype-specific IgG and OPA levels were similar regardless of the time interval after the initial vaccination. There was no difference in the safety profiles among the subgroups. In conclusion, administration of a second dose of PPSV23 at least 5 years after the initial vaccination was immunogenic and well-tolerated in the elderly ≥70 years of age regardless of the time interval after the initial vaccination.